Methodological quality of systematic reviews on treatments for depression: a cross-sectional study. (2nd May 2017) - Chung, V. C. H.; Wu, X. Y.; Feng, Y.; Ho, R. S. T.; Wong, S. Y. S.; Threapleton, D.
Abstract : Aims: Depression is one of the most common mental disorders and identifying effective treatment strategies is crucial for the control of depression. Well-conducted systematic reviews (SRs) and meta-analyses can provide the best evidence for supporting treatment decision-making. Nevertheless, the trustworthiness of conclusions can be limited by lack of methodological rigour. This study aims to assess the methodological quality of a representative sample of SRs on depression treatments. Methods: A cross-sectional study on the bibliographical and methodological characteristics of SRs published on depression treatments trials was conducted. Two electronic databases (the Cochrane Database of Systematic Reviews and the Database of Abstracts of Reviews of Effects) were searched for potential SRs. SRs with at least one meta-analysis on the effects of depression treatments were considered eligible. The methodological quality of included SRs was assessed using the validated AMSTAR (Assessing the Methodological Quality of Systematic Reviews) tool. The associations between bibliographical characteristics and scoring on AMSTAR items were analysed using logistic regression analysis. Results: A total of 358 SRs were included and appraised. Over half of included SRs ( n = 195) focused on non-pharmacological treatments and harms were reported in 45.5% ( n = 163) of all studies. Studies varied in methods and reporting practices: only 112 (31.3%) took the risk of bias among primary studies into account when formulating conclusions; 245 (68.4%) did not fully declare conflict of interests; 93 (26.0%) reported an ' a priori ' design and 104 (29.1%) provided lists of both included and excluded studies. Results from regression analyses showed: more recent publications were more likely to report ' a priori ' designs [adjusted odds ratio (AOR) 1.31, 95% confidence interval (CI) 1.09–1.57], to describe study characteristics fully (AOR 1.16, 95% CI 1.06–1.28), and to assess presence of publication bias (AOR 1.13, 95% CI 1.06–1.19), but were less likely to list both included and excluded studies (AOR 0.86, 95% CI 0.81–0.92). SRs published in journals with higher impact factor (AOR 1.14, 95% CI 1.04–1.25), completed by more review authors (AOR 1.12, 95% CI 1.01–1.24) and SRs on non-pharmacological treatments (AOR 1.62, 95% CI 1.01–2.59) were associated with better performance in publication bias assessment. Conclusion: The methodological quality of included SRs is disappointing. Future SRs should strive to improve rigour by considering of risk of bias when formulating conclusions, reporting conflict of interests and authors should explicitly describe harms. SR authors should also use appropriate methods to combine the results, prevent language and publication biases, and ensure timely updates.